Paradigma Pengetahuan Barat dan Islam: (Analisis Kritis Pemikiran Teori Belajar Dalam Perspektif Psikologi Islam) - Raikhan, Raikhan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2014)
Learning is a necessity and plays an important role in human life. This is because humans are born knowing nothing, and they are only supplied with physical and spiritual potential. So it is reasonable to see why and how humans are affected by how they learn. Therefore, learning is done by humans continuously, lifelong (life long education), at school or outside school, guided or not. This premise is reinforced by the fact that humans despite its weakness, but on the other hand it is a dynamic creature rather than a static being. With his dynamic, he is able to create progress with a variety of sophisticated technologies to simplify his life. The ideal thing that should happen in a learning process is not only in the form of transfer, but also transformation; be it knowledge, skills, and value. Therefore, learning must touch three domains, namely cognitive, psychomotor and affective. In the Islamic perspective, the learning process can not be separated from the human way of using the potential / tools given by God. From the perspective of Islam, man was awarded three tools in seeking knowledge: the five senses (jismiah), the mind (nafsiyah), and the heart (ruhiyah).